Prevalence, risk factors and behavioural and emotional comorbidity of acute seizures in young Kenyan children: a population-based study - Kariuki, SM; Abubakar, A; Kombe, M; Kazunga, M; Odhiambo, R; Stein, A; Newton, CRJC (BioMed Central, 2018)
Background: Acute symptomatic seizures and febrile seizures are common in children admitted to hospitals in Africa and may be markers of brain dysfunction. They may be associated with behavioural and emotional problems, but there are no published community-based studies in Africa. Methods: We screened 7047 children aged 1–6 years (randomly sampled from 50,000 in the community) for seizures (using seven questions) and invited those who screened positive and a proportion of negatives for a clinical assessment. Risk factors were identified using a parental questionnaire. Behavioural and emotional problems were examined using the Child Behaviour Checklist (CBCL) in 3273 children randomly selected from 7047. Generalised linear models with appropriate link functions were used to determine risk factors and associations between behavioural or emotional problems and acute seizures. Sobel–Goodman mediation tests were used to investigate if the association between acute seizures and CBCL scores was mediated by co-diagnosis of epilepsy. Results: Acute seizures were identified in 429 (6.1%) preschool children: 3.2% (95% confidence interval CI: 2.9–3.5%) for symptomatic seizures, and 2.9% (95% CI: 2.6–3.3%) for febrile seizures. Risk factors for acute seizures included family history of febrile seizures (odds ratio OR = 3.19; 95% CI: 2.03–5.01) and previous hospitalisation (OR = 6.65; 95% CI: 4.60–9.63). Total CBCL problems occurred more frequently in children with acute seizures (27%; 95% CI: 21–34%) than for those without seizures (11%; 95% CI: 11–12%; chi-squared p ≤ 0.001). Acute seizures were associated with total CBCL problems (adjusted risk ratio (aRR) = 1.92; 95% CI: 1.34–2.77), externalising problems (aRR = 1.82; 95% CI: 1.21–2.75) and internalising problems (aRR = 1.57; 95% CI: 1.22–2.02), with the proportion of the comorbidity mediated by a co-diagnosis of epilepsy being small (15.3%; 95% CI: 4.5–34.9%). Risk factors for this comorbidity included family history of febrile seizures (risk ratio (RR) = 3.36; 95% CI: 1.34–8.41), repetitive acute seizures (β = 0.36; 95% CI: 0.15–0.57) and focal acute seizures (RR = 1.80; 95% CI: 1.05–3.08). Conclusions: Acute seizures are common in preschool children in this area and are associated with behavioural and emotional problems. Both conditions should be assessed and addressed in children.